Find the general solution and the second solution of,
x2y"-3xy'+4y=0,given y1(x)=x2
Answer:-
Given that "y_1(x)=x^2" is one solution.
"\\implies y'_1=2x\\\\\n\\implies y''_1=2"
Given D.E "x^2y"-3xy'+4y=0"
Now "x^2y_1''-3xy'_1+4y_1=x^2(2)-3x(2x)+4x^2=0"
That is. "y_1(x)" satisfies the given DE
So "y_1(x)" s a solution of the D.E.
Let the second solution be "y_2(x)=u(x)x^2"
"\\implies y_2'=u'x^2+2ux\\\\\\implies y''_2=u''x^2+2u'x+2[u'x+u]"
or "y_2''=u''x^2+4u'x+2u"
Substitute these into the differential equation to get
"x^2(u''x^2+4u'x+2u)-3x(u'x^2+2ux)+4ux^2=0"
"\\implies u''x^4+u'x^3=0\\\\\n\\implies u''x+u'=0\\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ (\\because x >0) \\\\\n\\implies \\frac{u''}{u'}=-\\frac{1}{x}"
on integrating we get
"lnu'=-lnx+c\\\\\n\\ \\ \\ \\ \\ \\ \\ \\ =ln(\\frac{1}{x})+c"
By taking c=0 we get
"lnu' =ln(\\frac{1}{x})\\\\\n\\implies u'=\\frac{1}{x}\\\\\n\\implies u=lnx"
So second solution "y_2(x)=(lnx)x^2"
"W(x)=\\begin{vmatrix}\n x^2 & x^2lnx\\\\\n 2x & 2xlnx+x\n\\end{vmatrix}"
Now wronskian
"=2x^3lnx+x^3-2x^3"
"=x^3\n\\\\\\implies \\boxed{W(x)\\ne0} \\ \\ \\ \\ \\ \\ (\\because x >0)"
Hence "y_1(x) and Y_2(x)" form a fundamental set of solutions.
So general solution is given by
"\\boxed{y=c_1x^2+c_2x^2lnx}"
Comments
Leave a comment